2011
DOI: 10.1161/circulationaha.111.030213
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging of an Unusual Case of Right Ventricular Lipoma

Abstract: A 57-year-old man presented with mild dyspnea and fatigue on exertion. He had a history of hypertension and type 2 diabetes mellitus. The results of the physical examination were normal, with the exception of a grade II ejection systolic murmur over the aortic area. ECG showed normal sinus rhythm. An echocardiogram was performed for evaluation of cardiac murmur.Transthoracic echocardiogram showed a bicuspid aortic valve, with mild aortic stenosis (peak gradient, 16 mm Hg), but no regurgitation. Cardiac functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Of all cases of cardiac lipoma, only 10 tumors were found in the right ventricle (4.8%), of these, 6 patients were from case reports and the other 4 cases were reported respectively in 2 large-scale retrospective studies. 14–21 These articles were selected for review and are summarized below in the discussion of the literature (Table 2). In the present case study, during surgery, a lipoma was identified on the apex of the RV and the right side of IVS, which involved the chordae of the tricuspid valve, and the location was consistent only with the findings of Nishi.…”
Section: Discussionmentioning
confidence: 99%
“…Of all cases of cardiac lipoma, only 10 tumors were found in the right ventricle (4.8%), of these, 6 patients were from case reports and the other 4 cases were reported respectively in 2 large-scale retrospective studies. 14–21 These articles were selected for review and are summarized below in the discussion of the literature (Table 2). In the present case study, during surgery, a lipoma was identified on the apex of the RV and the right side of IVS, which involved the chordae of the tricuspid valve, and the location was consistent only with the findings of Nishi.…”
Section: Discussionmentioning
confidence: 99%
“…Of all cases of cardiac lipoma, only 10 tumors were found in the right ventricle (4.8%), of these, 6 patients were from case reports and the other 4 cases were reported respectively in 2 large-scale retrospective studies. [14][15][16][17][18][19][20][21] These articles were selected for review and are summarized below in the discussion of the literature (Table 2). In the present case study, during surgery, a lipoma was identified on the apex of the RV and the right side of IVS, which involved the chordae of the tricuspid valve, and the location was consistent only with the findings of Nishi.…”
Section: Epidemiology and Pathologymentioning
confidence: 99%
“…Chest x-rays revealed no signs of cardiomegaly or pulmonary oedema. The electrocardiography showed a sinus rhythm with premature atrial complexes and T wave abnormalities from lead V 4 to lead V 6 .…”
mentioning
confidence: 99%
“…1,2 According to the literature, 25% of cardiac lipomas are intramyocardial, 25% are extracavitary of epicardial origin and 50% are intracavitary of subendocardial origin; those of the right atrium are extremely rare. 5,6 Case HistoryA 71-year-old Caucasian woman presented to the emergency department with acute exacerbation of a 2-year history of recurrent dyspnoea and a new onset manifestation of hypertensive crisis. She did not complain of angina.…”
mentioning
confidence: 99%
See 1 more Smart Citation